Alternative alamat myths and legends from the Philippines : an anthology - Malonzo, Mervin; Chikiamco, Paolo (Tuttle Publishing, 2022)
Dip into the rich treasure trove of Filipino alamat (legends) with this new collection of contemporary short stories. This anthology includes works by a dozen talented and award-winning Filipino writers including Budjette Tan (Trese) and Eliza Victoria (Dwellers). Explore richly imagined realms where powerful gods and magical creatures are responsible for the twists and turns of fate in the lives of ordinary people.